ChemInform Abstract: Organic Reactions in Water or Biphasic Aqueous Systems under Sonochemical Conditions. A Review on Catalytic Effects. Issue 18 (May 2015) - Cravotto, Giancarlo; Borretto, Emily; Oliverio, Manuela; Procopio, Antonio; Penoni, Andrea
Abstract Review: 35 refs.